OPTIMALISASI YOUTUBE SEBAGAI MEDIA DAKWAH BAGI GENERASI MILENIAL - Nanik Rahmawati; Yazida Ichsan; Muhammad Syafrizal Pahlevi; Nur Nawangsih; Latsa Alya Utami (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
Da'wah is an effort made by someone in distributing Islamic knowledge or information. Da'wah is delivered in various forms, namely direct or indirect. In the modern era or often referred to as the millennial era, it has become a trend that the delivery of da'wah is done online, this is very supportive of the current state of society which requires us to learn and keep getting extensive information even though we are in the atmosphere of the Covid-19 pandemic.This study uses qualitative research where the case is in the form of descriptive data in the form of an observed analytical statement. In general, qualitative research is research based on people's lives, history, behavior, and social activities. One of the reasons for using a qualitative approach is the experience of researchers who found and understood the optimization of YouTube as a medium of propaganda for the millennial generation.The results of the study are that nowadays youtube is also often used as a medium of da'wah, supported by circumstances that currently require people to stay at home. Youtube is very suitable and recommendations are used for preaching. The implementation of the da'wah strategy through Youtube social media, namely: (1) For consumptive planning such as the routine activities of the Koran week and recitations; (2) Promotion of pesantren to attract students; (3) To study the Koran, especially the pronunciation of the hijaiyah letters; (4) To recite books and others.